2006
DOI: 10.1038/sj.emboj.7600954
|View full text |Cite
|
Sign up to set email alerts
|

Iron-responsive degradation of iron-regulatory protein 1 does not require the Fe–S cluster

Abstract: The generally accepted role of iron-regulatory protein 1 (IRP1) in orchestrating the fate of iron-regulated mRNAs depends on the interconversion of its cytosolic aconitase and RNA-binding forms through assembly/disassembly of its Fe-S cluster, without altering protein abundance. Here, we show that IRP1 protein abundance can be ironregulated. Modulation of IRP1 abundance by iron did not require assembly of the Fe-S cluster, since a mutant with all cluster-ligating cysteines mutated to serine underwent iron-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
109
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(120 citation statements)
references
References 54 publications
(99 reference statements)
11
109
0
Order By: Relevance
“…4B). For IRP1 the decrease is readily explained by the common observation that apo-IRP1 lacking its Fe/S cluster is more prone to degradation (26,35). Because IRP2 protein levels are negatively regulated by the iron availability in the cytosol (34), our results suggest that cytosolic iron was diminished.…”
Section: Fdx2 Depletion Adversely Affects Cellular Iron Metabolism Insupporting
confidence: 46%
“…4B). For IRP1 the decrease is readily explained by the common observation that apo-IRP1 lacking its Fe/S cluster is more prone to degradation (26,35). Because IRP2 protein levels are negatively regulated by the iron availability in the cytosol (34), our results suggest that cytosolic iron was diminished.…”
Section: Fdx2 Depletion Adversely Affects Cellular Iron Metabolism Insupporting
confidence: 46%
“…6A, second panel from top). We as well as others have observed that the apo form of IRP1 is less stable than the iron-replete form (18,33,34). Consistent with this, Irp1 protein levels also decline upon Iop1 knock-out (Fig.…”
Section: Resultssupporting
confidence: 72%
“…1A). Thiol mutagenesis and modification analyses have revealed that IRP1 C437 is critical for not only [4Fe-4S] coordination but also IRP1 RNA binding and protein stability (7,23,38,51). Sequence alignment between IRP1 and IRP2 shows that seven of the nine cysteine residues in human IRP1 are conserved in human IRP2, including the three cysteines required for IRP1 [4Fe-4S] cluster binding (IRP2 C512, C578, and C581) (Fig.…”
Section: Resultsmentioning
confidence: 99%